2020
DOI: 10.3390/ijerph17134772
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dietary Intake and Nutritional Status in CrossFit-Trained Individuals: A Descriptive Study

Abstract: CrossFit is a discipline with high training and nutritional requirements. To date, there is only scarce data evaluating nutrition among CrossFit training and they mostly focus on selected nutritional interventions. Therefore, the purpose of this descriptive study was the assessment of dietary intake and nutritional status in a selected group of CrossFit-trained participants. The study consisted of 62 CrossFit athletes (31 men and 31 women, aged 31.0 ± 5.2 and 30.0 ± 4.3 years, respectively). Body compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 61 publications
3
25
1
6
Order By: Relevance
“…The results of our study indicated that even without taking supplementation into account, phosphorus and sodium intake in the diets of the studied athletes exceeded the daily recommendations. Similar study results in terms of increased sodium consumption were found in those training in judo [43], CrossFit [44], and soccer [22]. During days of intense training (especially in the heat), a greater amount of water and sodium are lost in sweat.…”
Section: Discussionsupporting
confidence: 80%
“…The results of our study indicated that even without taking supplementation into account, phosphorus and sodium intake in the diets of the studied athletes exceeded the daily recommendations. Similar study results in terms of increased sodium consumption were found in those training in judo [43], CrossFit [44], and soccer [22]. During days of intense training (especially in the heat), a greater amount of water and sodium are lost in sweat.…”
Section: Discussionsupporting
confidence: 80%
“…Unfortunately, incorrect food choices are common, and non-adherence to dietary recommendations has been noted in various groups directly related to sport. Thus far, inadequate food choices were confirmed in physical education students from different countries [ 7 , 8 , 9 , 10 , 11 , 12 ] and in professional and semi-professional athletes [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In sports training, it is necessary to consider the effectiveness of skeletal muscle activity and assess body response in relation to pre-established exercise, observing strength, endurance, and muscle activity [22,23]. Therefore, it is justi able to evaluate the electromyographic behavior of the masseter and temporalis muscles of participants who practice CrossFit exercise to understand whether there is a relationship between high-intensity sports and the functionality of the dynamic structures of the stomatognathic system.…”
Section: Discussionmentioning
confidence: 99%